Valorization of chitin biomass into N-containing chemical 3-acetamido-5-acetylfuran catalyzed by simple Lewis acid. (December 2022) - Zang, Hongjun; Feng, Yimo; Zhang, Mingchuan; Wang, Kai; Du, Yannan; Lv, Yaxin; Qin, Zixian; Xiao, Yunfei
Abstract: 3-Acetamido-5-acetylfuran(3A5AF) is a nitrogen-containing fine chemical and has broad application prospects and high research value. Herein, we report a mild and efficient method for the synthesis of 3A5AF from N-acetyl-d -glucosamine (NAG). The influence of solvent, temperature and additive on the catalytic performance was also studied. The Lewis acids with high catalytic efficiency have been smoothly screened. The highest yield (41.57%) of 3A5AF was obtained in the presence of B2 O3 and MgCl2 ·6H2 O at 180 °C for 60 min under normal atmospheric conditions. The reaction pathway was explored by LC-MS, 1 H NMR, 13 C NMR and FT-IR spectra. Compared with the microwave method and hydrothermal method, the optimized reaction condition was relatively mild. Moreover, the catalyst MgCl2 ·6H2 O is low-cost and environmentally friendly. Graphical abstract: Image 1 Highlights: NAG was converted to 3A5AF in 41.57% yield in a period of 60 min under normal atmospheric conditions. MgCl2 .6H2 O was a low-cost, environmentally friendly and promising catalyst for the conversion of chitin biomass. The possible reaction pathways were proposed.